2004
DOI: 10.1177/0583102404048517
|View full text |Cite
|
Sign up to set email alerts
|

Eddy Current Damping in Structures

Abstract: When a conductive material is subjected to a time-varying magnetic flux, eddy currents are generated in the conductor. These eddy currents circulate inside the conductor generating a magnetic field of opposite polarity as the applied magnetic field. The interaction of the two magnetic fields causes a force that resists the change in magnetic flux. However, due to the internal resistance of the conductive material, the eddy currents will be dissipated into heat and the force will die out. As the eddy currents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(44 citation statements)
references
References 48 publications
1
41
0
Order By: Relevance
“…The results present in this paper will be useful for gaining a deeper understanding of the transient effects encountered in eddy current damping [21], braking [22], and maglev transportation [19,23,24] as well as for Lorentz force eddy current non-destructive testing [25] applications.…”
Section: Introductionmentioning
confidence: 94%
“…The results present in this paper will be useful for gaining a deeper understanding of the transient effects encountered in eddy current damping [21], braking [22], and maglev transportation [19,23,24] as well as for Lorentz force eddy current non-destructive testing [25] applications.…”
Section: Introductionmentioning
confidence: 94%
“…Sodano and Bae [9] and Bae et al [10,11] have already presented a good literature review. Kwak et al [12] introduced an eddy current damper (ECD) and applied it to the vibration suppression of a cantilever beam.…”
Section: Introductionmentioning
confidence: 99%
“…Since it is rather difficult to implement maintenance and the operational environment is severe in aerospace, the damping device should be advanced in long function fatigue life, high reliability, and good applicability in vacuum and heat transformation conditions. Eddy current dampers (ECDs), with instinct natures such as Engineering, Beihang University, PR China non-contact, non-leakage and easy implementation, become a candidate to suppress vibrations of a system for aerospace applications (Sodano and Bae, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In his research, the dynamic behavior of the ECD is analyzed and it is found that the force/velocity ratio of the damper significantly varies with temperature. Sodano and Bae (2004) review various types of eddy current damping mechanisms used in different structures and systems, including the applications utilized in space field. In addition, the future of eddy current dampers with some potential uses that have not yet been studied is discussed in his article.…”
Section: Introductionmentioning
confidence: 99%